Management of vulvar hypoplasia by performing episiotomy in cow - a case report - Rajoria, J S; Singh, A P; Tomar, Priyanshu; Prashant; Ningwal , Deepak (Animal Reproduction Update, 2023)
A crossbred cow was admitted with the history of dystocia was examined and diagnosed as a case of dystocia due to congenital vulvar stenosis. Per vaginal examination of a crossbred heifer presented for the treatment of dystocia revealed vulvar stenosis and persistent hymen. Episiotomy followed by the excision of transverse band of persistent hymen lead to per vaginal delivery of fetus.